Modeling and Simulation of Track Clamp Jacking System based on Bond Graph theory - Chen Suli; Fan Yansong; Wang Wei; Ren Fushen (Jixie chuandong)
When the gear rack drilling rig for slant drilling is working,string collar need to accurate alignment through certain angle of tilt and different position,and move up and down relative to the derrick,the oilwell string makeup and breakout device such as the traditional hydraulic tongs and iron roughneck is not suitable for it. Focused on the technical problem,the track clamp system which can track freely along the rig derrick is proposed,its jacking system and hydraulic control system are designed. Based on bond graph theory,the mathematical model of track clamp jacking system is established,and the dynamic equation is derived. Based on the20- Sim software,the dynamic simulation analysis is carried out,the rationality of the bond graph model is validated,and the causes and effects of the system dynamic characteristics are analyzed,which provide technical support and theoretical guidance for the research and control of track clamp jacking system.